2014
DOI: 10.1080/00103624.2014.954717
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pretransplant Basal and Split Applications of Nitrogen on the Growth and Yield of Manawthukha Rice

Abstract: A field experiment was conducted to investigate the effects of pretransplant basal (surface application, BSF, and incorporation methods, BIC) and split applications of nitrogen (N) on the growth and yield parameters of rice. Using 120 kg N ha −1 except (N0, control), different percentages of N rate were applied at basal, tillering, and panicle initiation in five N split treatments. Growth parameters and dry matter were greater in BIC than BSF until panicle initiation stages. Among N split applications, N2 (25:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…In this method, one portion is applied before tillage as a basal N fertilizer, and the other is used as topdressing during later growth (Wang et al, ). Split application minimizes inorganic N leaching and enhances N use efficiency (Moe et al, ). Nevertheless, the topdressing application requires extra labor and is inconvenient during the later growth period.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, one portion is applied before tillage as a basal N fertilizer, and the other is used as topdressing during later growth (Wang et al, ). Split application minimizes inorganic N leaching and enhances N use efficiency (Moe et al, ). Nevertheless, the topdressing application requires extra labor and is inconvenient during the later growth period.…”
Section: Introductionmentioning
confidence: 99%
“…4 Influence of experimental treatments on SPAD-chlorophyll measurement (A-B) of aromatic rice during 2017 and 2018; DDSR = Dry direct-seeded rice; TPR = Transplanted rice; HSD = Honestly significant difference; a HSD = HSD value for 2017; b HSD = HSD value for 2018; N = Nitrogen management pattern; Bars (treatment mean ± standard error, n = 3) sharing different lettering for a parameter above the bar are different significantly (p ≤ 0.05) by the Tukey's HSD test within same year; NS = Not significant at P > 0.05; ** = Significant at P < 0.01 Feng et al 2020). The split application of N at critical growth stages (tillering or PI) coincides with crop demand and resulted in better performance of crop (Moe et al 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Increasing basal dose of N without any split before transplanting or seeding led to serious consequences in the rice fields. Heavy basal dose led to increasing N losses in the form of surface runoff, NH 4 volatilization and resulted in lower yields (Moe et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…From the full heading to maturity stage, the decrease rate of root dry weight and root activity was delayed under W1 with an increasing ratio of topdressing fertilizer, but to what extent of the increase needs to be further studied. Root growth and elongation, leaf photosynthetic capacity, and adaptability to AWD were enhanced under AWD couple N2, while the potential decline in N3 treatment may be caused by very few basal fertilizer amounts, and the whole rice plant can still absorb basal fertilizer from the soil after full heading ( Moe et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The N 15 tracer method revealed that nitrogen absorbed during early growth is used mainly in the vegetative period ( Ata-Ul-Karim et al, 2017 ; Wang et al, 2017b ). Excessive fertilizer application at the early growth stages reduce root length, surface area, volume, and CGR at the later growth stages ( Moe et al, 2014 ). Excess or deficient nitrogen temporarily promotes early root growth.…”
Section: Introductionmentioning
confidence: 99%